2009
DOI: 10.1111/j.1364-3703.2008.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

PVYNTN elicits a diverse gene expression response in different potato genotypes in the first 12 h after inoculation

Abstract: Host gene expression changes in the early response to potato virus Y(NTN) interaction were compared in two differently sensitive potato cultivars: the resistant cultivar Santé and the sensitive cultivar Igor. Hybridization of potato TIGR cDNA microarrays allowed us to monitor the expression of approximately 10,000 genes simultaneously at 0.5 and 12 h post-inoculation (hpi). Microarray data, analysed by statistics and data mining, were complemented by subtraction library construction and sequence analysis to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 44 publications
6
96
0
Order By: Relevance
“…2459-Mock (2184). In addition, a previous study reported that in potato, a greater number of differentially expressed genes are found in susceptible than in resistant cultivars in the later stage of Potato virus Y (PVY) infection [25]. Our results were in agreement with it when the total number of polymorphic fragments in susceptible line Acc.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2459-Mock (2184). In addition, a previous study reported that in potato, a greater number of differentially expressed genes are found in susceptible than in resistant cultivars in the later stage of Potato virus Y (PVY) infection [25]. Our results were in agreement with it when the total number of polymorphic fragments in susceptible line Acc.…”
Section: Discussionsupporting
confidence: 90%
“…Because the survival of the obligate pathogens such as viruses lies on the nutrition provided from host plants, and virus infection makes plants changing gene expression patterns and the content of metabolisms to support virus proliferation. It has been suggested that gene expression of host plants infected with pathogens change predominantly in susceptible plants, especially during the late infection stage [25][27]. Indeed, the total number of polymorphic fragments observed in susceptible line Acc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers for PR-1b were designed as described in [14] and were 5′-GTATGAATAATTCCACGTACCATATGTTC-3′ (forward primer) and 5′-GTGGAAACAAGAAGATGCAATACTTAGT-3′ (reverse primer).…”
Section: Methodsmentioning
confidence: 99%
“…Baebler et al (2009) detected differences in expression of hundreds of genes as soon as half an hour after inoculation of potato leaves with PVY NTN . Signalling and defence responses specific to cv.…”
Section: Effects Of Viruses On Potato Gene Expressionmentioning
confidence: 99%